Training to curb police corruption in developing countries: A suggested framework - Hope, Kempe Ronald (International journal of police science & management, 2017)
Most of the anti-corruption training that currently exists for the police in developing countries lacks an appropriate focus and is not provided in the manner of a coherent concentration. It tends to be delivered primarily in the form of police orientation to existing anti-corruption laws, or other criminal laws in general. It also does not provide a thorough understanding of the phenomenon of corruption and how it looks within policing practice in the society, nor does it impart even basic knowledge and skills on how to adhere to professional standards and avoid the temptation of accepting gifts, favors or gratuities, or engaging in other corrupt acts. The purpose of this work is to set out one suggested model of a basic training framework and approach for curbing police corruption in developing countries pursuing democratic policing. It outlines learning goals and training objectives, proposes a training approach model, suggests training content and coverage, and indicates the expected outcomes from the training approach and process. The article draws on the author’s fieldwork experience in police anti-corruption and ethics training, and assessments of best practices in training to improve police integrity and ethical behavior in developing countries. It advocates for the application of problem-based learning as the most appropriate and successful training approach method to curb police corruption in developing countries.